Cyberpunk: Snow Crash by Neal Stephenson and Hard boiled Wonderland and end of the World by Haruki Murakami - Akshaya, A. (International Journal of Psychosocial Rehabilitation, 2020)
The present studies are based on the topic of cyber punk, which is a literary device and a fact that is related to real world. To make the paper more informative and fruitful, the two novels are included, both of them are based on application of scientific technology and effects to mankind, they are Hard Boiled wonderland and The End of the world by Haruki Murakami and Snow Crash by Neal Stephenson . This study shows how cyberpunkism has progressed throughout the following period of time. Both of the works are eminent and has created breakthrough in the cyberpunk literature. After reading the two novels it is identified that even though the both of the writers are from two different continents their views about the idea of cyberpunk world is quite unique and they were also able to point out its relevance in the futuristic world.